Persepsi Guru Penjas Terhadap Pembelajaran Daring di Tengah Pandemi Covid-19 Pada SMA Negeri Se-Kabupaten Jepara - Muhammad Izzama Indra Indra; Pandu Kresnapati; Fajar Ari Widiyatmoko (Journal of Physical Activity and Sports (JPAS), 2020)
The purpose of this research is to see the perceptions of physical education teachers towards courageous learning in the midst of the Covid-19 pandemic at Public High Schools in Jepara Regency. There are also benefits, namely as an evaluation material for the knowledge of Physical Education teachers in SMA Negeri Jepara Regency. This research is a quantitative study using descriptive methods (Descriptive Research). The data of this study were sourced from the results of a survey on filling out a questionnaire by 28 Physical Education teachers in SMA Negeri Jepara Regency, in this case the teacher became a research. The data collected individually is descriptive based so that it does not seek explanations, hypotheses, make predictions, or learn implications. The results of this study indicate that the perceptions of Physical Education teachers towards courageous learning in the midst of the Covid-19 pandemic at Public High Schools throughout Jepara Regency are in the "very unsupporting" category by 18% (5 teachers), the "unsupporting" category is 43% (12 teachers), the "supporting" category was 25% (7 teachers), the "very supportive" category was 14% (4 teachers). So it can be concluded that the perception of sports Physical Education teachers towards online learning in the midst of the Covid-19 pandemic at SMA Negeri Jepara Regency is in the "unsupported" category. Suggestions for other researchers would be better if you use open questionnaires or interviews, respondents are more directly and carefully monitored at the time of data collection, so that the resulting data is more valid and for further researchers to use further instruments in this study     Keywords: Physical education teacher responses, online learning, Covid-19 Abstrak Tujuan peneletian ini untuk mengetahui persepsi guru pendidikan jasmani terhadap pembelajaran daring di tengah pandemi covid-19 pada SMA Negeri Se-Kabupaten Jepara. Ada juga manfaatnya yaitu Sebagai bahan evaluasi terutama bagi pengetahuan para guru penjasorkes di SMA Negeri Se Kabupaten Jepara. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan metode deskriptif (Descriptive Research). Data penelitian ini bersumber dari hasil survey pengisian angket oleh 28 guru penjas di SMA Negeri Se-Kabupaten Jepara, dalam hal ini guru tersebut menjadi responden penelitian. Data yang dikumpulkan semata-mata bersifat deskriptif sehingga tidak bermaksud mencari penjelasan, menguji hipotesis, membuat prediksi, maupun mempelajari implikasi. Hasil penelitian ini menunjukkan bahwa persepsi guru Pendidikan Jasmani olahraga terhadap pembelajaran daring di tengah pandemi covid-19 pada SMA Negeri Se-Kabupaten Jepara berada pada kategori “sangat tidak menunjang” sebesar 18% (5 guru), kategori “tidak menunjang” sebesar 43% (12 guru), kategori “menunjang” sebesar 25% (7 guru), kategori “sangat menunjang” sebesar 14% (4 guru). Sehingga dapat disimpulkan bahwa persepsi guru Pendidikan Jasmani olahraga terhadap pembelajaran daring di tengah pandemi covid-19 pada SMA Negeri Se-Kabupaten Jepara masuk dalam kategori “tidak menunjang”. Saran bagi peneliti lain akan lebih baik jika menggunakan angket terbuka atau wawancara, responden lebih dipantau secara langsung dan cermat pada saat pengambilan data, sehingga data yang dihasilkan lebih valid dan bagi peneliti selanjutnya agar lebih menyempurnakan instrumen yang digunakan dalam penelitian ini.   Kata kunci: Tanggapan guru penjas, pembelajaran daring, Covid-19